SUSTAINABLE COMPETITIVE ADVANTAGE MODEL OF UMKM: THE EXISTENCE OF TECHNOLOGICAL INNOVATION AND MARKET ORIENTATION AS A PREDICTOR - Setyawati, Amelia; Seseli, Eka Merdekawati Imelda; Kusuma, Rr. Chusnu Syarifa Diah; Setyawati, Christina Yanita (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
The main objective of the research is to analyze the effect of technological innovation and market orientation on sustainable competitive advantage. The sample in this study amounted to 180 respondents, determined by the convenience sampling approach. Data collection uses a questionnaire instrument which is then distributed online. Data analysis uses the SPSS application by displaying data processing results through research instrument tests with validity and reliability tests, multiple regression analysis, coefficient of determination, and hypothesis testing. Based on the results of data analysis, it is stated that technological innovation and market orientation have a positive and significant effect on sustainable competitive advantage. The research implications explain that it is important for SMEs to improve their ability to adopt new technologies and develop technological innovations needed in their business. MSMEs can seek assistance from various sources, such as governments, business organizations, and financial institutions, to access the resources and information needed to adopt new technologies and develop technological innovations that can help them gain a competitive advantage. Furthermore, to overcome the problem of market orientation in MSMEs, efforts are needed to increase understanding of market needs, utilize market research, focus on market needs and wants, have a clear marketing strategy, and increase available resources